The sound of life and everything - Van Dolzer, Krista (New York, NY : G. P. Putnam's Sons, an imprint of Penguin Group (USA), 2015)
In 1950s California, grieving Mildred Clausen tries to have her son, who was killed in World War II, cloned but instead, a Japanese man emerges and her niece, Ella Mae, befriends him, in spite of the town's intense prejudice and her aunt's conviction that he is her son's killer.
Keywords: Family life -- California -- Fiction; Prejudices -- Fiction; Japanese -- United States -- Fiction; Cloning -- Fiction; California -- History -- 20th century -- Fiction; Families -- California -- Juvenile fiction; Prejudices -- Juvenile fiction; Japanese -- United States -- Juvenile fiction; Cloning -- Juvenile fiction; California -- History -- 20th century -- Juvenile fiction